Many waters - Engle, Madeleine L (Time quintet, 1986)
The fifteen-year-old Murry twins, Sandy and Dennys, are accidentally sent back to a strange Biblical time period, in which mythical beasts roam the desert and a man named Noah is building a boat in preparation for a great flood.